(untitled) (Studia Doctoralia Psychology and Educational Science, 2024)
The aim of thist study is to analyze the relationships between emotional self-regulation and the most prevalent psychological disorders at the moment, anxiety and depression. At the same time, we aim to investigate the moderating role of empathy in tjis relationship. The study was conducted on a sample of 145 participants aged between 20 and 46, M = 23.89, SD = 5.33. The instruments used were Emotion Regulation Questionnaire, Toronto Empathy Questionnaire, and Depression, Anxiety and Stress Scale (subscales for depression and anxiety). The results highlighted that ineffective emotional self-regulation is significantly and positevely associeted with anxiety. However, emotional ineffective self-regulation was not significantly associeted with depression. According to the results, empathy does not moderate the relationship between innefective emotional self-regulation and anxiety. The results of our study emphasise the necessity for giving a special attention to the factors involved in anxiety and depression, including emotional self-regulation and empathy.